EVALUATION OF PHARMACEUTICAL STORAGE MANAGEMENT IN PRIMARY CLINICS BASED ON PHARMACEUTICAL SERVICE QUALITY INDICATORS - Astuti, Briandini Dwi (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2026)
Drug storage is a critical stage in pharmaceutical logistics management to ensure the quality of pharmaceutical preparations and budget efficiency. Inappropriate storage can trigger drug damage, expiration, and medication errors. Objective: This study aims to evaluate drug storage indicators in the pharmacy installation warehouse of a primary clinic. Methods: This research is a descriptive observational study with retrospective and prospective data collection. Indicators measured include the compatibility of physical stock with stock cards, the percentage of dead stock, the percentage of expired/damaged drugs, and the suitability of storage systems (alphabetical, FIFO, FEFO, and LASA). Results: The results showed that the percentage of match between the number of drugs and stock cards was 98.5%. The dead stock percentage was 7.29%, and expired drugs accounted for 0.72%. The placement of Look-Alike Sound-Alike (LASA) drugs and the implementation of alphabetical, FIFO, and FEFO systems both achieved 100% compliance. Conclusion:Overall, the drug storage system has met the efficiency indicator standards, although mitigation steps are still needed to minimize dead stock and optimize pharmaceutical supply management, thereby preventing financial loss.